Grand Tour of the World China - Ed. Winchester, Kenneth (Torstar Books Inc, 1986)
Introduces the history and culture of China from Beijing to Tibet, as well as Taiwan, Hong Kong, and Macao, and provides facts for travelers
Keywords: China Hong Kong (China) Macao Macau (China) Science; General Taiwan